Anti-Cancer Nanopowders and MAPLE-Fabricated Thin Films Based on SPIONs Surface Modified with Paclitaxel Loaded β-Cyclodextrin - Rebecca Alexandra Puiu; Paul Cătălin Balaure; Ema Constantinescu; Alexandru Mihai Grumezescu; Ecaterina Andronescu; Ovidiu-Cristian Oprea; Bogdan Stefan Vasile; Valentina Grumezescu; Irina Negut; Ionela Cristina Nica; Miruna Silvia Stan (MDPI AG, 2021)
Globally, cancer is the second most common cause of death, and Europe accounts for almost 25% of the global cancer burden, although its people make up only 10% of the world's population. Conventional systemically administered anti-cancer drugs come with important drawbacks such as inefficiency due to poor bioavailability and improper biodistribution, severe side effects associated with low therapeutic indices, and the development of multidrug resistance. Therefore, smart nano-engineered targeted drug-delivery systems with tailored pharmacokinetics and biodistribution which can selectively deliver anti-cancer agents directly to the tumor site are the solution to most difficulties encountered with conventional therapeutic tools. Here, we report on the synthesis, physicochemical characterization, and in vitro evaluation of biocompatibility and anti-tumor activity of novel magnetically targetable SPIONs based on magnetite (Fe3O4) nanoparticles' surface modified with β-cyclodextrin (CD) and paclitaxel (PTX)-guest-host inclusion complexes (Fe3O4@β-CD/PTX). Both pristine Fe3O4@β-CD nanopowders and PTX-loaded thin films fabricated by MAPLE technique were investigated. Pristine Fe3O4@β-CD and Fe3O4@β-CD/PTX thin films were physicochemically characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), thermal analysis, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The biocompatibility of bare magnetic nanocomposite thin films was evaluated by MTT cell viability assay on a normal 3T3 osteoblast cell line culture and by measuring the level of NO in the culture medium. No significant modifications, neither in cell viability nor in NO level, could be observed, thereby demonstrating the excellent biocompatibility of the SPIONs thin films. Inverted phase-contrast microscopy showed no evident adverse effect on the morphology of normal osteoblasts. On the other hand, Fe3O4@β-CD/PTX films decreased the cell viability of the MG-63 osteosarcoma cell line by 85%, demonstrating excellent anti-tumor activity. The obtained results recommend these magnetic hybrid films as promising candidates for future delivery, and hyperthermia applications in cancer treatment.